Cell death and inflammation during obesity: "Know my methods, WAT(son)" - Hildebrandt, Ximena; Ibrahim, Mohamed; Peltzer, Nieves (Cell death and differentiation, 2023)
Obesity is a state of low-grade chronic inflammation that causes multiple metabolic diseases. During obesity, signalling via cytokines of the TNF family mediate cell death and inflammation within the adipose tissue, eventually resulting in lipid spill-over, glucotoxicity and insulin resistance. These events ultimately lead to ectopic lipid deposition, glucose intolerance and other metabolic complications with life-threatening consequences. Here we review the literature on how inflammatory responses affect metabolic processes such as energy homeostasis and insulin signalling. This review mainly focuses on the role of cell death in the adipose tissue as a key player in metabolic inflammation.